Indonesian students’ use of Chat Generative Pre-trained Transformer in essay writing practices - Sodiq, Syamsul; Rokib, Mohammad (Institute of Advanced Engineering and Science, 2024)
The proliferation of the Chat Generative Pre-trained Transformer (ChatGPT) in the educational area has become a debatable topic. ChatGPT has proven to be appealing to students as a helpful resource in their learning journey, specifically in enhancing their proficiency in essay writing practices. Following this, the study endeavored to scrutinize the purpose and behavior of students employing ChatGPT for composing essays in the Indonesian language. Utilizing a quantitative methodology, the research centered on collecting and analyzing numerical data. The study employed a questionnaire as the research instrument, utilizing a 5-point Likert scale. The questionnaire was administered to 303 second-semester students enrolled in an essay writing course. The findings of the study revealed that the majority of students utilized ChatGPT to enhance their comprehension of essay writing concepts, bolster their confidence, and receive valuable feedback. The findings from the data analysis indicated that students perceived ChatGPT as a valuable resource for enhancing grammar and sentence structure, fostering creativity, and cultivating robust ideas and arguments.